Проектирование теплообменных аппаратов для ГТУ сложных циклов - Кузнецов, В. В.; Соломонюк, Д. Н. (НТУ "ХПИ", 2008)
Modes of perfection of designing technology of the heat-exchange apparatuses for GTP compound cycles are presented. Results of comparison of mass and overall dimensions smooth pipes surfaces and surfaces with intensification of the heat transfer are received.
Keywords: КПД; котлы-утилизаторы; воздухоохладители; рекуператоры; интенсифицированные поверхности